AN ECOLOGICAL STUDY ON THE LENTIC WATER BODY OF BANIYAPUR WITH REFERENCE TO PLANKTONIC DIVERSITY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Ecology is the study of the relationship between living organism, including humans, and their physical environment, it seeks to understand vital connection between plants and animals and the world around them. Ecology is the multidisciplinary field extending across the physical, biological, and social sciences. Ecology was the practical interest early in human history.